VIEWS OF MATHEMATICAL MODELS IN THE DISCOVERY OF COMPUTER LINGUISTICS - Boqiyeva Marjona Shuhratovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article provides an insight into the specific trends and models of computer linguistics that are emerging at a time when information technology is evolving. Mathematical models can also be considered in accordance with modern requirements. The origins of mathematical linguistics can be traced back to computer linguistics, and the article discusses this.